2023
DOI: 10.3390/genes14112021
|View full text |Cite
|
Sign up to set email alerts
|

When Mast Cells Run Amok: A Comprehensive Review and Case Study on Severe Neonatal Diffuse Cutaneous Mastocytosis

Emilian-Gheorghe Olteanu,
Mihaela Bataneant,
Maria Puiu
et al.

Abstract: Neonatal diffuse cutaneous mastocytosis (NDCM) is defined as the infiltration of the epidermis by a clonal proliferation of mast cells, observed at birth, without initial signs of systemic involvement. The typical driver mutation is in the KIT gene. We report a rare case of a boy, born at term, already presenting at birth with generalized subcutaneous nodules on the face, scalp, trunk, back, hands, and feet. The spleen, liver, and inflammatory markers were normal at birth. Tryptase was significantly elevated. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…According to current knowledge, genetic drivers, epigenetics, and both hormonal and metabolic factors involved in the pathogenesis of pediatric mastocytosis are poorly understood [ 1 , 3 , 8 ]. However, numerous studies show that children with DCM can carry different somatic mutations in exon 17 of KIT (D816V, D816Y, or D816I), as well as mutations in other exons (Del419, K509I, or internal tandem duplication A502_Y503dup) [ 18 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Familial mastocytosis is a specific form of the disease in which mostly germline KIT mutations are detected in affected family members [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Genetic Background Of Diffuse Cutaneous Mastocytosismentioning
confidence: 99%
See 2 more Smart Citations
“…According to current knowledge, genetic drivers, epigenetics, and both hormonal and metabolic factors involved in the pathogenesis of pediatric mastocytosis are poorly understood [ 1 , 3 , 8 ]. However, numerous studies show that children with DCM can carry different somatic mutations in exon 17 of KIT (D816V, D816Y, or D816I), as well as mutations in other exons (Del419, K509I, or internal tandem duplication A502_Y503dup) [ 18 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Familial mastocytosis is a specific form of the disease in which mostly germline KIT mutations are detected in affected family members [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Genetic Background Of Diffuse Cutaneous Mastocytosismentioning
confidence: 99%
“…Furthermore, numerous studies have shown that rubbing and scratching of the skin, sudden temperature changes (such as hot baths or exposure to heat), teething, viral infections, or vaccinations may induce blistering or provoke other MC mediator-related symptoms [ 13 , 28 , 40 , 58 , 59 ]. A brief review of case reports on DCM, published since 1962, is presented in Table 2 [ 28 , 35 , 36 , 38 , 39 , 40 , 41 , 52 , 53 , 54 , 58 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Clinical Presentation Of Diffuse Cutaneous Mastocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive blistering, presenting as both small vesicular lesions and large hemorrhagic bullae, is a dominant clinical manifestation in infancy (Figure 5), while a leather-like appearance and hyperpigmentation (brown or yellow colour of the skin) develops in the further course of DCM [7,9,43,52,54,55]. DCM is associated with severe MC mediator-related symptoms and a higher risk of anaphylactic shock than in other forms of CM [39,42,48,50,54,58,59]. The large MC infiltration of the infant's entire skin and an unfavorable ratio of the body weight to body surface area are the reasons for DCM patients usually presenting with elevated serum tryptase levels [7,9,26,42,53].…”
Section: Clinical Characteristic Of Skin Involvement In Children With CMmentioning
confidence: 99%
“…In children with CM, the most common are cutaneous MC mediator-related symptoms, including pruritus, flushing, blistering and dermographism, regardless of the subtype of CM [39,41,47,59]. Pruritus is the most commonly reported symptom [6].…”
Section: Mast Cell Mediator-related Symptoms and Anaphylaxis In Child...mentioning
confidence: 99%